Effects of agmatine on cognitive functions during vascular dementia in biological aging through eNOS and BDNF expression - ARICIOĞLU, FEYZA (TAYLOR & FRANCIS LTD, 2017)
Objective: Biological aging has been recognized to cause impairment of memory and the development of vascular dementia. Based on our previous work, agmatine has been shown to have a beneficial effect and might have therapeutic potential on cognitive functions, including learning and memory. The aim of the present study was to examine the possible effect of agmatine on biological aging-induced vascular endothelial dysfunction and associated dementia in rats. Methods: We used three different age groups (4-month-olds, 18-month-olds and 24-montholds; n = 12 in each group) of control and agmatine-treated rats. Control animals received physiological saline for 8 weeks. Agmatine sulfate (40 mg/kg, twice daily) was given to the agmatine groups orally for 8 weeks. Herein, we investigated the effects of agmatine on systolic blood pressure (SBP), nitric oxide (NO)-mediated endothelium-dependent and - independent vasorelaxant responses in thoracic aorta, cognitive performance (passive avoidance test; PAT, and Morris water maze test; MWMT), endothelial nitric oxide synthase (eNOS) expression and both hippocampal and amygdaloid brain-derived neurotrophic factor (BDNF) expression in aged rats. Results: We found cognitive decline, endothelial dysfunction and reduced eNOS and BDNF expression in aged rats. All these changes may result from aging-induced vascular dementia. We also found that chronic treatment with agmatine may improve amygdala-dependent emotional and spatial learning and memorial performance, and endothelial function, and may regulate eNOS and BDNF protein expression in aged rats. Conclusion: Results of the current study point out that chronic agmatine treatment may prevent endothelial dysfunction associated with vascular dementia through eNOS and BDNF expression in aged rats.
Keywords: Aging; agmatine; passive avoidance; Morris water maze; vascular dementia; NITRIC-OXIDE SYNTHASE; AGE-RELATED-CHANGES; SPRAGUE-DAWLEY RATS; LONG-EVANS RATS; ALZHEIMERS-DISEASE; REGIONAL-VARIATIONS; BLOOD-PRESSURE; YOUNG-ADULT; L-ARGININE; MEMORY